Restrukturyzacja gospodarki Wielkopolski - podstawy programu - Wojtasiewicz, Lucyna (Wydział Prawa i Administracji UAM, 1992)
In order to overcome economic recession and achieve economic growth it is necessary to modernize the economy and increase the productivity. It pertains to the whole territory of Poland, and thus also to Wielkopolska region. Although Wielkopolska region in many respects looks better than other parts of Poland, Wielkopolska also faces many problems to be solved, i.a. liquidation of unemployment, development of transport and some other spheres of public economy, as well as improvement of environmental protection. The restructuring of the region's economy is necessary. The first task to be implemented is the technological restructuring. Of great importance is also the selection of new motoric forces which could stimulate the growth of the whole region. Besides, one should not neglect the restructuring of ownership structure (privatization of the state sector). In the growth of the economy of Wielkopolska the leading role should be ascribed to innovative industries, to food-processing industry and to some services of supra-regional character (Poznań International Fair, transit). One should apply the following three scenarios: 1. activities of self-government authorities aimed at encouraging foreign investment; 2. creating incentives for new Polish companies by local authorities; 3. initiating a complex governmental and self-governmental programme aimed at finding innovative capital. The above tasks must be accompanied by legal and organizational reforms.
Restructuring Wielkopolska region economy - the foundations of the programme